2013
DOI: 10.1007/s00701-013-1863-1
|View full text |Cite
|
Sign up to set email alerts
|

Falcine venous plexus within the falx cerebri: anatomical and scanning electron microscopic findings and clinical significance

Abstract: The falcine venous plexus is a network of venous channels that exists within the connective tissue of the falx; the sizes and patterns of communication of these structures showed regional differences. Neurosurgeons should be aware of the regional differences when making an incision or puncturing the falx during a surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…12) Tatarli et al concluded that the falcine venous plexus exhibited different anatomical patterns in the anterior, middle, and posterior portions of the falx cerebri and that falcine sinuses were different patterns according to their location. 13) But an important distinction should be made between the rare persistent fetal falcine sinus and the falcine venous plexus. 14) …”
Section: Discussionmentioning
confidence: 99%
“…12) Tatarli et al concluded that the falcine venous plexus exhibited different anatomical patterns in the anterior, middle, and posterior portions of the falx cerebri and that falcine sinuses were different patterns according to their location. 13) But an important distinction should be made between the rare persistent fetal falcine sinus and the falcine venous plexus. 14) …”
Section: Discussionmentioning
confidence: 99%
“…Even if cerebral angiography shows that the venous sinuses are completely obstructed by the tumor, sufficient collateral circulation is not guaranteed to have developed, and the possibility of impaired venous perfusion or venous infarction associated with venous sinus transection cannot be ignored. [19][20][21] Because preoperative cerebral angiography did not reveal ISS obstruction, preservation of the ISS as well as the SS was regarded as important, and incisions were made in the tentorium and falx cerebri while all the venous sinuses were preserved in all four of our patients.…”
Section: Discussionmentioning
confidence: 94%
“…Previous descriptions of the supratentorial innervation have been crude and inconsistent, including the medical illustrations that appear in both textbooks and journal articles (Drake et al 2009;Gilroy et al 2009;Moore et al 2009;Kemp et al 2012;Bauer et al 2005). Accurate knowledge of the anatomy of the venous sinuses in the dura mater is important during neurosurgery involving the arteriovenous fistula or when resecting meningiomas and other types of brain tumours (Tubbs et al 2007;Tatarli et al 2013;Xu et al 2013;Tanaka, 2015;Amato et al 2016;Shibao et al 2016), and so the present study investigated the straight and transverse sinuses adjacent to the tentorium cerebelli in order to elucidate the course of the nervus tentorii.…”
Section: Discussionmentioning
confidence: 99%